Chemo-Radiotherapy of Oligometastases of Colorectal Cancer With Pegylated Liposomal Mitomycin-C Prodrug (Promitil): Mechanistic Basis and Preliminary Clinical Experience - Tahover, Esther; Bar-Shalom, Rachel; Sapir, Eli; Pfeffer, Raphael; Nemirovsky, Igor; Turner, Yehonatan; Gips, Maya; Ohana, Patricia; Corn, Benjamin W.; Wang, Andrew Z.; Gabizon, Alberto A. (Frontiers in Oncology, 2018)
Hypo-fractionated radiotherapy and stereotactic body radiotherapy are viable options for treatment of oligometastases. A prodrug of mitomycin-C is under clinical testing as a pegylated liposomal formulation (Promitil) with an improved safety profile over mitomycin-C. Promitil was offered to two patients with oligometastases from colorectal cancer as radiosensitizer. Each derived durable clinical benefit from Promitil administered immediately prior to and following irradiation. Transient toxicity to normal tissues of moderate to severe degree was observed. Promitil appears to have potential clinical value in this setting.